DAMPAK KEBERADAAN GRAND MALL TERHADAP TINGKAT PENDAPATAN PEDAGANG DI PASAR BATANGASE, KABUPATEN MAROS - Nirmayanti Nirmayanti; Dalilul Falihin (Universitas Negeri Makassar, 2023)
This research was conducted to find out (1) what is the description of the income of traders in the Batangase Market before the existence of the Grand Mall and after the existence of the Grand Mall, (2) what is the impact of the Grand Mall on the level of income of traders in the Batangase Market, (3) what efforts have been made to minimize the impact the existence of the Grand Mall on the level of income of traders in Batangase Market. The research method used is a qualitative research method with a descriptive approach. Data collection techniques using observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation and conclusion. The results of the study show 1) the description of merchant income before the Grand Mall was very profitable because many visitors came, after the Grand Mall had an impact on merchant income, merchant income decreased. 2) the impact of the existence of the Grand Mall consists of positive and negative impacts, namely a) the positive impact is the development of an area in Maros Regency, as the largest and most comfortable shopping center, and as a vacation or recreation center b) the negative impact is a decrease in income traders, traffic jams and floods. 3) efforts made to minimize the impact of the existence of the Grand Mall on the income level of traders in Batangase Market, namely a) maintaining market cleanliness and security b) improving service quality c) completing market facilities d) building good relations between traders and buyers e) conducting promotions goods and discounts.